Reconstruction of Educational Qualifications for Members of the House of Representatives and DPRD in the Election Law - Ismaidar; Br Sembiring, Tamaulina; Efendi Rangkuti, Ewin (Universitas Muhammadiyah Palu, 2025)
This study aims to discuss in depth the juridical study and the role of members of the House of Representatives in a democratic country, as well as comprehensively discuss the urgency of reconstructing the law on the educational qualifications of members of the House of Representatives in election law. The type of research is normative juridical with a descriptive-analytical approach, discussing existing legal symptoms and problems and testing them based on laws regulations, and legal norms. The results of this study show that the legislative institution has a strategic position because it plays a role in carrying out the functions of legislation, budgeting, and supervision, as stipulated in Article 20 of the Constitution of the Republic of Indonesia of 1945. The requirements to become a legislative member are regulated in Article 240 Paragraph (1) of Law Number: 7 of 2017 concerning Elections, namely: being over 21 years old, fearing God Almighty, being loyal to Pancasilan and the 1945 Constitution, and having at least a high school, madrasah aliyah, vocational high school, or other equivalent school. The urgency of reconstructing the law on the educational competence of legislative members in Law Number: 7 of 2017 concerning Elections, namely the provisions of Article 240 to improve the educational qualifications of legislative members. Higher educational qualifications can affect the ability to make decisions, absorb aspirations, increase public credibility and trust, and adapt to the needs of the times